Why Overriding Mandatory Provisions that Protect Financial Stability Deserve Special Treatment. (24th April 2014) - Berends, André J.
Abstract The EU Bank Recovery and Resolution Directive provides tools to deal effectively with unsound or failing banks. Some provisions of this directive are designated as overriding mandatory provisions as referred to in Article 9 Rome I Regulation. The author analyses the effectiveness of the designation of a rule as an overriding mandatory provision, given the principle of private international law that parties can choose the applicable law and the competent forum. His conclusion is that in an international context overriding mandatory provisions are not always as overriding or as mandatory as they may seem at first sight. This may be acceptable with regard to 'normal' overriding mandatory provisions. However, the author argues that financial stability is so important that overriding mandatory provisions that protect financial stability need special treatment.